Використання кривих Лоренца для оцінки рівномірності розподілу сільськогосподарських угідь в екоагровиробництві - Чорна, Ніна Олександрівна; Chorna, Nina (Дніпровський державний аграрно-економічний університет, 2015)
Розглянуто особливості розподілу сільськогосподарських угідь між вітчизняними аграрними підприємствами. Оцінено ступінь концентрації земельних угідь, які їм належать. Запропоновано для аналізу рівномірності розподілу сільськогосподарських угідь використовувати криві Лоренца та інші агротехнологічні ресурси. Сформульовано методологічні аспекти застосування кривих Лоренца для практичного використання в аграрному виробництві. The present state of the agricultural ecological production and distribution of agricultural land. Articulated the need for effective greening of agricultural production, which involves the use of complex organizational and economic measures and management decisions aimed at creating a sustainable agricultural ecosystems. Noted that an important factor of farming in Ukraine a significant degree of concentration of land area in agricultural enterprises. Among the main criteria of economic efficiency in the agricultural sector should be environmental and economic performance and requirements, which include the activation of economic incentive mechanisms of land protection activity, introduction of methods and techniques for efficient and environmentally sound use of land resources. Noted the need to reduce the degradation of soils for reducing their use of chemicals in the ground, excessive plowing, improper irrigation, erosion. The priority areas of improving the agro-economic transformation of the AIC should be regarded as a scientifically based optimization of the ratio between the major components of agricultural landscapes (arable land, permanent crops, hayfields, pastures), taking into account the specialization, concentration and distribution of branches. Compliance with the rules of crop rotation will allow for the natural reproduction of the soil. Aspects of the application of the Lorenz curve for the statistical processing of the uniform distribution of agricultural land, and examples of its use in practice, an example of distribution of agricultural land between agricultural enterprises in Ukraine.
Use for evaluation Lorenz curve uniform distribution of agricultural lands for eco- agroproduction
Keywords: сталий розвиток; state development; екологізація; greening; сільськогосподарські угіддя; farmland; аграрні підприємства; farms; методи статистичного аналізу; methods of statistical analysis; інформаційні технології; information technology; кумулятивні частки; cumulative shares; криві Лоренца; the Lorenz curve